The Structures of Conquest: Debating Extractivism(s), Infrastructures and Environmental Justice for Advancing Post-Development Pathways - Alexander Dunlap (Revue Internationale de Politique de Développement)
The green economy and ‘green growth’ are not solutions to ecological and climate catastrophe. The dominate trajectory of techno-industrial development has to be reconsidered and placed within ecological limits. The ‘social’, related to environmental and climate justice, tends towards subordinating the ecological in the maintenance of modernist infrastructures, and thus towards breaking efforts to achieve socio-ecological harmony. The following examines the realities of resource extractivism, but also tensions within academic debates on these matters. This entails locating an important ‘grey area’ within these debates, which has significant implications for imagining pathways to address ecological and climate catastrophe. This grey area—questioning the difference between extractivism and industrialism—also persists within archetypal positions on land acquisition and shades of reform in environmental justice studies, and, to a lesser degree, in the (academic) decolonial literature. This chapter contends that environmental justice reinforces modernist development, necessitating and expanding extractivism and ecologically destructive infrastructures. By highlighting ambiguities in critical literatures, it seeks to provide political clarity, reinforcing personal and collective self-determination and, secondarily, to encourage public policy to begin taking climate catastrophe seriously.